2016
DOI: 10.15761/docr.1000143
|View full text |Cite
|
Sign up to set email alerts
|

Caries levels among autistic children in Khartoum State, Sudan. A step towards improving the well-being of less fortunate children

Abstract: Objectives: To determine caries levels among autistic children and compare it to that of non-autistic children.Methodology: It is a cross-sectional comparative study; that compared autistic and non-autistic children. The data was collected from autism centers and private schools in Khartoum, Bahri and Omdurman. With sample size of 132, 44 autistic children, 88 non autistic children. Data was collected using interviews of the children's parents/guardian and oral clinical examination to assess dental caries usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…No study of this type is available for Italy. This work is meant as a first step in this direction and it is in line with similar works performed for other countries [19][20][21][22][23][24][25][26][27].…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…No study of this type is available for Italy. This work is meant as a first step in this direction and it is in line with similar works performed for other countries [19][20][21][22][23][24][25][26][27].…”
Section: Introductionsupporting
confidence: 72%
“…Finally, while some authors have reported that caries experience in children with ASD is comparable or even less severe than in control groups [20][21][22][23]26,37], others [13] suggest a worsening of caries experience associated with ASD. In our case, a rigorous comparison is not possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Nonong et al, found (82.6%) ASD children in their study have strong preference to cariogenic foods and (52.17%) they consumed cariogenic foods three times a day or more. 27 Difference in research findings could be due to disproportionate sample size, differences in research instruments, and differences in parenting patterns. 28 Table 2 shows that the DMFT and deft indices of ASD children are at a moderate level.…”
Section: Discussionmentioning
confidence: 99%